Review of the genus Hartemita Cameron, 1910 (Hymenoptera, Braconidae, Cardiochilinae), with the description of six new species from Vietnam - Long, Khuat Dang (Pensoft Publishers, 2011)
Abstract. The Oriental and East Palaearctic genus Hartemita Cameron, 1910 (Braconidae: Cardiochilinae) is recorded for the first time from Vietnam. Sixteen species of the genus Hartemita are currently recognized from Oriental and East Palaearctic regions. One species is newly recorded for Vietnam, Hartemita singaporensis (Mao, 1945)and six new species from Vietnam are described and illustrated: Hartemita coffeana sp. n., Hartemita daklaka sp. n., Hartemita khuatbaolinhae sp. n., Hartemita similis sp. n., Hartemita maculata sp. n. and Hartemita vietnamica sp. n. A key to species of the genus Hartemita Cameron is included.